Lactone Backbone Density in Rigid Electron‐Deficient Semiconducting Polymers Enabling High n‐type Organic Thermoelectric Performance. Issue 7 (18th December 2021) - Alsufyani, Maryam; Stoeckel, Marc‐Antoine; Chen, Xingxing; Thorley, Karl; Hallani, Rawad K.; Puttisong, Yuttapoom; Ji, Xudong; Meli, Dilara; Paulsen, Bryan D.; Strzalka, Joseph; Regeta, Khrystyna; Combe, Craig; et al.
Abstract: Three lactone‐based rigid semiconducting polymers were designed to overcome major limitations in the development of n‐type organic thermoelectrics, namely electrical conductivity and air stability. Experimental and theoretical investigations demonstrated that increasing the lactone group density by increasing the benzene content from 0 % benzene (P‐0), to 50 % (P‐50), and 75 % (P‐75) resulted in progressively larger electron affinities (up to 4.37 eV), suggesting a more favorable doping process, when employing (N‐DMBI) as the dopant. Larger polaron delocalization was also evident, due to the more planarized conformation, which is proposed to lead to a lower hopping energy barrier. As a consequence, the electrical conductivity increased by three orders of magnitude, to achieve values of up to 12 S cm and Power factors of 13.2 μWm −1  K −2 were thereby enabled. These findings present new insights into material design guidelines for the future development of air stable n‐type organic thermoelectrics. Abstract : Three new n‐type semiconducting polymers, P‐0, P‐50, and P‐75 are developed, in which the lactone group densities were maximized by increasing the benzene content from 0 % benzene (P‐0), to 50 % (P‐50), and 75 % (P‐75), to enable co‐planar polymers with deep‐lying LUMO energy level. As a result, the polymer of P‐75 exhibits a good thermoelectric performance with a maximum electrical conductivity of 12 S cm ‐1 and figure of merit power factor of 13.2 μWm ‐1  K ‐2 .